Cell Signaling Pathways That Promote Radioresistance of Cancer Cells - Michel M. Ouellette; Sumin Zhou; Ying Yan (Diagnostics, 2022)
Radiation therapy (RT) is a standard treatment for solid tumors and about 50% of patients with cancer, including pediatric cancer, receive RT. While RT has significantly improved the overall survival and quality of life of cancer patients, its efficacy has still been markedly limited by radioresistance in a significant number of cancer patients (intrinsic or acquired), resulting in failure of the RT control of the disease. Radiation eradicates cancer cells mainly by causing DNA damage. However, radiation also concomitantly activates multiple prosurvival signaling pathways, which include those mediated by ATM, ATR, AKT, ERK, and NF-κB that promote DNA damage checkpoint activation/DNA repair, autophagy induction, and/or inhibition of apoptosis. Furthermore, emerging data support the role of YAP signaling in promoting the intrinsic radioresistance of cancer cells, which occurs through its activation of the transcription of many essential genes that support cell survival, DNA repair, proliferation, and the stemness of cancer stem cells. Together, these signaling pathways protect cancer cells by reducing the magnitude of radiation-induced cytotoxicity and promoting radioresistance. Thus, targeting these prosurvival signaling pathways could potentially improve the radiosensitivity of cancer cells. In this review, we summarize the contribution of these pathways to the radioresistance of cancer cells.